Prevalence of immunological marker (Anti-GAD) in patients with type 1 diabetes : hospital based study - Thabit, Maral F.; Abduljabbar, Hana A.; Abid, Shayma G. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: type 1diabetes (T1DM) is a form of diabetes mellitus that results from autoimmune destruction of insulin-producing beta cells of the pancreas, leading to permanent insulin deficiency ,categorized as either being positive or negative for various auto antibodies related to pancreatic function .An anti glutamic acid decarboxylase autoantibody(Anti-GAD) is recognized as one of the major serological markers for type 1 diabetes mellitus. Objectives: to determine the prevalence of the immunological marker (Anti-GAD) among a sample of type1diabetus mellitus patients and to identify some factors that might be associated with its seroposivity. Method: A cross-sectional retrospective study was carried out during February to May, 2011 in specialized diabetic clinic of Children Welfare Teaching Hospital, Baghdad .The study sample included 120 type1diabetus patients for whom(Anti-GAD) had been determined, patients reports were studied and analyzed statistically. Results: The demographic characteristics of this studied sample with higher percentage 57.5% of females, 46.7%in the age group 10-14 years, 12.5% had family history of other autoimmune diseases and the majority 69.2% had healthy Body Mass Index (BMI).while the clinical characteristics revealed higher percentage 47% with onset of the disease (5-9) years, 64.2% having a duration of disease (1-4)years ,86.7% presented with classical type of presentation and 52.5% had good control of diabetes . The prevalence of Anti-GAD in this studied sample was 66.7%. Seropositivity of Anti-GAD was significantly associated with delayed age of patients at diagnosis with mean age (7.5± 3.25) years, short duration of the diseases with mean (3.85±2.57) years, female gender (65%) compared to (35%) of male gender had positive Anti-GAD test, while seropositivity of Anti-GAD was not related to other study variables (age of patients, control of diabetes mellitus, BMI, and family history of other autoimmune disease). Conclusions: High prevalence of Anti-GAD and its titer in this studied sample, seropositivity was related mainly to female gender, delayed age at diagnosis and short duration of diabetes.